FACTORS AFFECTING EMPLOYEE TURNOVER IN MULTINATIONAL COMPANIES IN MALAYSIA (Malaysian Management Journal, 2022)
The purpose of this research paper is to investigate the factors affecting employee turnover in multi-national companies in Malaysia. The descriptive research design is used with the view of getting an expansive explanation about problems and factors affecting employee turnover in multi-national companies in the country. A quantitative research method has been used to quantify the problem by way of generating numerical data that can be transformed into usable statistics. To collect data, the study distributed a survey questionnaire to a total of 250 respondents. The findings showed that job dissatisfaction and work-life imbalance have a significant positive relationship to employee turnover. The study also found that training & development programs has a negative relationship with employee turnover. Lastly, the study has also found that, rewards system had either no, or less positive significant relationship with employee turnover in MNCs in Malaysia. The study has provided some recommendations on how to prevent the problem of high employee turnover in multi-national companies in Malaysia. Employees were found to have certain views about work-related matters, especially when it concerned their getting a balanced work-life and being consulted for the training & development programs to be more efficient and productive. The findings have also provided some implications that can contribute to guiding government or policy makers that will ensure a positive working environment for all employees.